Creative technologies for multidisciplinary applications - Connor, Andy M. 1972-; Marks, Stefan, 1973- (Advances in media, entertainment, and the arts (AMEA) book series, 2016)
Because creative technology encompasses many applications with the realm of art, gaming, the humanities, and digitization, this book features a diverse collection of relevant research for the modern world. It is a pivotal reference publication for educators, students, and researchers in fields related to sociology, technology, and the humanities